2010
DOI: 10.1111/j.1755-9294.2010.01080.x
|View full text |Cite
|
Sign up to set email alerts
|

ORIGINAL ARTICLE: Morphometric evaluation for relationship of atherosclerosis developed in coronary and peripheral muscular arteries: An autopsy study

Abstract: Background and aims:Atherosclerosis is a systemic disorder that develops in any blood vessel of the body. Atherosclerosis can result in fatal complications such as myocardial infarction or stroke. The aim of this study was to compare the severity of atherosclerosis between the coronary arteries and other peripheral arteries. To our knowledge, no such morphometric tissue studies through autopsy samples so far are available in Korea. Methods: The left anterior descending artery, right coronary artery and bilater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…In addition, other previous studies have shown that patients with LEAD is often present with coronary atherosclerosis, and have an increased risk for adverse cardiovascular events [14]. Jeong et al [15] found in an autopsy study that, peripheral arteries including the carotid artery can be helpful in clinical prediction of CAD. However, such predictions should also include other risk factors such as age, hypertension, diabetes and dyslipidemia and other relevant clinical conditions.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, other previous studies have shown that patients with LEAD is often present with coronary atherosclerosis, and have an increased risk for adverse cardiovascular events [14]. Jeong et al [15] found in an autopsy study that, peripheral arteries including the carotid artery can be helpful in clinical prediction of CAD. However, such predictions should also include other risk factors such as age, hypertension, diabetes and dyslipidemia and other relevant clinical conditions.…”
Section: Discussionmentioning
confidence: 96%